2020
DOI: 10.1007/s42865-020-00024-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the potential role of atmospheric particulate pollution and airborne transmission in intensifying the first wave pandemic impact of SARS-CoV-2/COVID-19 in Northern Italy

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which exploded in Wuhan (Hebei Region, China) in late 2019, has later spread around the world, causing pandemic effects on humans. During the first wave of the pandemic, Italy, and especially its Northern regions around the Po Valley, faced severe consequences in terms of infected individuals and casualties (more than 31,000 deaths and 255,000 infected people by mid-May 2020). While the spread and effective impact of the virus is primarily relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 100 publications
2
8
0
Order By: Relevance
“…A positive and significant correlation was observed between the PM10 and Pm2,5 particles AQI; this is consistent with the results of studies conducted in 120 cities in China and Milan, where COVID-19 disease is widespread (57)(58). One of the reasons for the spread of COVID-19 in Milan was recognized to be the concentration of environmental pollutants, such as PM10, which exceeded their limits (59)(60). This could be because the particles of the COVID-19 virus attach to the contaminants and use them as a carrier to be transported.…”
Section: Discussionsupporting
confidence: 89%
“…A positive and significant correlation was observed between the PM10 and Pm2,5 particles AQI; this is consistent with the results of studies conducted in 120 cities in China and Milan, where COVID-19 disease is widespread (57)(58). One of the reasons for the spread of COVID-19 in Milan was recognized to be the concentration of environmental pollutants, such as PM10, which exceeded their limits (59)(60). This could be because the particles of the COVID-19 virus attach to the contaminants and use them as a carrier to be transported.…”
Section: Discussionsupporting
confidence: 89%
“…There are two different mechanisms that may create a causal relationship between fine particulate air pollution and SARS-CoV-2 infections. The first is that particulate matter might carry the airborne virus, transmitting it into the human respiratory system ( Copat et al, 2020 ; Martelletti and Martelletti, 2020 ; Di Girolamo, 2021 ; Nor et al, 2021 ). The second is that fine particulate matter could increase the severity of the Covid-19 disease by delaying or complicating recovering ( Domingo and Rovira, 2020 ; Leifer et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…With data for the last four years, they found evidence of positive correlations of high concentrations of PM 10 , PM 2.5 , NO 2 and O 3 on COVID-19 cases in 71 Italian provinces. Indications of particulate matter pollution as a carrier of the SARS-CoV-2 virus was found by Di Girolamo (2021) for Northern Italy using satellite data and a microphysical model. The latter was applied to model the transmission of the virus by air.…”
Section: Introductionmentioning
confidence: 99%
“…Comunian et al [139] published a review article about air pollution and COVID-19 by stressing the role of particulate matter in its spreading. Girolamo et al [140] assessed the potential role of atmospheric particulate pollution and airborne transmission in intensifying the first wave pandemic impact of SARS-CoV-2/COVID-19 in Northern Italy. It is found that the number of small potentially infectious particles coalescing on PM2.5 (particulate matter 2.5 micrometers or less in diameter) and PM10 (particulate matter 10 micrometers or less in diameter) particles is estimated to exceed the number of infectious particles needed to activate COVID-19 infection in humans.…”
Section: Mathematical Models That Simulate the Role Of Aerosols In Transmission Of Covid-19mentioning
confidence: 99%